2017
DOI: 10.1002/eap.1629
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar mixtures: a meta‐analysis of the effect of intraspecific diversity on crop yield

Abstract: Abstract. Extensive research has shown that greater plant community diversity leads to higher levels of productivity and other ecosystem services, and such increased diversity has been suggested as a way to improve yield and agricultural sustainability. Increasing intraspecific diversity with cultivar mixtures is one way to increase diversity in agricultural systems. We examined the relationship between intraspecific diversity and yield in cultivar mixtures using a meta-analysis of 91 studies and >3,600 observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
176
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 82 publications
(158 reference statements)
22
176
1
1
Order By: Relevance
“…The benefits of cultivar/varietal mixtures for increasing yield and reducing yield variability are small but consistent (Reiss & Drinkwater, ). Most mixture studies have focussed only on yield and have not considered the mechanisms which deliver the benefits; the main exception has been studies looking at reduced disease transmission (Newton et al ., ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The benefits of cultivar/varietal mixtures for increasing yield and reducing yield variability are small but consistent (Reiss & Drinkwater, ). Most mixture studies have focussed only on yield and have not considered the mechanisms which deliver the benefits; the main exception has been studies looking at reduced disease transmission (Newton et al ., ).…”
Section: Discussionmentioning
confidence: 90%
“…One partial solution to the need to maintain or boost agricultural productivity, whilst maintaining biodiversity, is the use of cultivar mixtures (Barot et al ., ). These have been demonstrated to show yield benefits in comparison to cropping with single varieties (Kiær et al ., ; Borg et al ., ; Reiss & Drinkwater, ). Using mixtures also reduces the year to year variation in yield (Smithson & Lenne, ; Reiss & Drinkwater, ), increasing the reliability of farmer incomes, and reduces the need for fungicide treatments as mixtures delay or reduce disease transmission (Newton et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown effects of plant genotypic diversity on productivity (Cook‐Patton et al. , Reiss and Drinkwater ), herbivore spatial distribution (Utsumi et al. , Zytynska et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expect genetic diversity at kin recognition systems in cultivated species to be much lower, if any, in elite varieties (Murphy, Swanton, Van Acker, & Dudley, ). Still, if polymorphism has been maintained, genetically based kin recognition may explain conflicting results among studies of variety mixtures within species (Reiss & Drinkwater, ; Smithson & Lenné, ) and the outcome of competition among varieties depending upon their genetic similarity at the kin recognition loci. Here, we did not find evidence that plants could direct helping toward relatives in durum wheat landraces from traditional agrosystems, where genetic diversity is still present at the field and individual levels (this study, Muller et al unpublished).…”
Section: Discussionmentioning
confidence: 99%